PERANAN ZAKAT, INFAK, SEDEKAH DALAM PENGEMBANGAN USAHA KECIL PADA OPERASIONAL BAITUL MAAL WAT TAMWIL - Fawza Rahmat (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
The Role of Zakat, Infak, and Sadaqah in the Development of Small Businesses in Baitul Maal Wat Tamwil (BMT) Operations. The rise of small businesses that support the community's economy is central to poverty alleviation. What plays a role when small businesses are the main issue of community-based economic solutions related to the Islamic religion through baitul mal wat tamwil. The method used to build this research is a literature review by collecting several reliable sources. As well as combining with various phenomena that occur in society. The phenomenon in society is that Baitul Maal Wat Tamwil is an economic institution that promotes saving activities and provides financing to small entrepreneurs. In addition, BMT is also equipped with Baitul Maal activities which are more social in nature. The joining of these two activities is very much needed in empowering the poor. In its operations, BMT implements the sharia system. Meanwhile, in theory Baitul Maal Wat Tamwil, which is abbreviated as BMT, is a supporting institution to improve the quality of small business entrepreneurs based on the sharia system. BMT can and should be used as a business partner for various small entrepreneurs in developing their business, because the partnership pattern is a practical form of a congregational way of carrying out all muamalah matters.